AN MCDM APPROACH FOR PERSONNEL SELECTION USING THE COCOSO METHOD - Popović, Milica (Journal of process management and new technologies, 2021)
Candidate selection has a direct impact on the quality of a company’s human resources department, so it’s an essential activity for public and private companies alike. Various ways have been created to assist and make it easier for organizations to select the best candidate, specifically the right people to do specific roles. As a result, the purpose of this study is to propose the use of multi-criteria decision-making techniques in personnel selection. Therefore, for the determination of the weights of the criteria will be employed the SWARA method, whereas, for the ranking of the alternatives, i.e. selection of the best candidate, a CoCoSo method will be applied.personnel selection